Morphological and anatomical investigation of New Caledonian graminoid Dendrobium (Orchidaceae) with the description of two new species - Pignal, Marc; Munzinger, Jérôme (European Journal of Taxonomy, 2020)
Morphological characters support the description of two new species of Orchidaceae from New Caledonia: Dendrobium butinii M.Pignal & Munzinger sp. nov. and Dendrobium letocartiorum Munzinger & M.Pignal sp. nov. The lectotypes of Dendrobium camaridiorum Rchb.f. and D. crassifolium Schltr. are designated here. A leaf anatomical study was conducted and provided useful characters to distinguish the five New Caledonian graminoid Dendrobiineae species. Two identification tools are provided: an anatomical key for sterile material of grass-like Dendrobiineae and a morphological key for the New Caledonian graminoid Dendrobium. We propose preliminary conservation assessments with IUCN criteria for the new taxa.